2017
DOI: 10.1111/hae.13220
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world resource use and costs of haemophilia A‐related bleeding

Abstract: These results suggest that initiating prophylaxis earlier in life may reduce the healthcare costs of bleeding events and their long-term complications. Future studies should strive to collect more detailed information on disease severity and treatment protocols to improve estimates of disease burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 22 publications
1
35
0
2
Order By: Relevance
“…In a recent analysis, the projected annual drug cost of prophylactic treatment in the US ranged from nearly $700,000 to $750,000 for standard and extended halflife FVIII products, respectively 9 . Separate studies have shown patients with hemophilia A incur higher costs due to greater rates of hospitalization, ER visits, office visits, medical procedures, and laboratory tests compared with the general population 7,14,15 . Greater indirect costs for these patients are driven by absenteeism and productivity loss 7,15 .…”
Section: Introductionmentioning
confidence: 99%
“…In a recent analysis, the projected annual drug cost of prophylactic treatment in the US ranged from nearly $700,000 to $750,000 for standard and extended halflife FVIII products, respectively 9 . Separate studies have shown patients with hemophilia A incur higher costs due to greater rates of hospitalization, ER visits, office visits, medical procedures, and laboratory tests compared with the general population 7,14,15 . Greater indirect costs for these patients are driven by absenteeism and productivity loss 7,15 .…”
Section: Introductionmentioning
confidence: 99%
“…The GEPHARD contains most of this information for paediatric patients. In secondary databases, bleeding events treated at home are not captured . Information on bleeds, treatment patterns, treatment of inhibitors, joint health and target joints is partially available, or not at all.…”
Section: Resultsmentioning
confidence: 99%
“…In secondary databases, bleeding events treated at home are not captured. 22 Information on bleeds, treatment patterns, treatment of inhibitors, joint health and target joints is partially available, or not at all. Examples are severe bleeds necessitating out-or inpatient treatment and treatment patterns based upon prescriptions.…”
Section: As Shown Inmentioning
confidence: 99%
“…Small sample size in the current study prevented analysis of costs by any characteristic; in fact, simple comparison of costs by sex may be misleading at this time. The mean total costs were $112,090 for an 18‐month period in the current study, compared with $96 918 for 1 year, not including prophylaxis, from one study including similar‐aged males 11 . The diagnosis confusion observed among females with HA, relative to males, can delay appropriate non‐emergent (ie, prophylactic) treatment.…”
Section: Discussionmentioning
confidence: 99%